2002
DOI: 10.1590/s0004-282x2002000500004
|View full text |Cite
|
Sign up to set email alerts
|

A house-to-house survey of epileptic seizures in an urban community of Rio de Janeiro, Brazil

Abstract: -Objective: To carry out a prevalence study about epileptic seizures and epilepsy in an urban lowincome population. Method: Prevalence study in a two-phase model: screening and diagnosis confirmation. It was applied a structured questionnaire in 982 people all effectively resident on March 1rst 2000 based on a population census previously carried out by the Nurse Faculty. One neurologist interviewed all the suspected cases. Results: It was detected 176 suspected cases of epileptic seizures: 156 with non-epilep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
19
1
1

Year Published

2002
2002
2019
2019

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 29 publications
(21 citation statements)
references
References 11 publications
0
19
1
1
Order By: Relevance
“…Gap examples include access to and availability of medical facilities [13,16,19,21,22] and medical diagnostic tools [16], appropriately trained medical care professionals [16,19,21], and diagnostic/ treatment facilities limited to larger cities and their surrounding areas, as these are usually serviced by at least one university hospital and several smaller hospitals and health care facilities. Cultural beliefs about ES [16,19,23], including stigmatization of people diagnosed with seizures, may also contribute to the treatment gap [19,21,22,24]. Other factors include limited knowledge of effective treatment options [18,21,22], high health care costs [16,21,22] and health insurance availability [16,19].…”
Section: Introductionmentioning
confidence: 99%
“…Gap examples include access to and availability of medical facilities [13,16,19,21,22] and medical diagnostic tools [16], appropriately trained medical care professionals [16,19,21], and diagnostic/ treatment facilities limited to larger cities and their surrounding areas, as these are usually serviced by at least one university hospital and several smaller hospitals and health care facilities. Cultural beliefs about ES [16,19,23], including stigmatization of people diagnosed with seizures, may also contribute to the treatment gap [19,21,22,24]. Other factors include limited knowledge of effective treatment options [18,21,22], high health care costs [16,21,22] and health insurance availability [16,19].…”
Section: Introductionmentioning
confidence: 99%
“…In the city of Porto Alegre in the state of rio Grande do sul, a cross-sectional study indicated an accumulated prevalence rate of 36.8/1000 for epilepsy 8 . In rio de Janeiro city, another study found an accumulated prevalence of 16.3/1000 cases 9 . In são José do rio Preto, são Paulo state 10 , a study of prevalence in the urban population was conducted and an accumulated prevalence of 18.6/1000 inhabitants, and 8.2/1000 for active epilepsy was found over the past two years.…”
mentioning
confidence: 95%
“…Seizures most often originate in amygdalo-hippocampal region, in the medial and basal portion of temporal lobe. Hence, mesial temporal epilepsy (MTE) is the most frequent focal epilepsy [29][30][31][32].…”
Section: Temporal Lobe Epilepsymentioning
confidence: 99%